The great American documents. Volume II, 1831-1900 - Ashby, Ruth (Hill and Wang, 2019)
"In the Great American Documents series, the teacher and graphic-book author Ruth Ashby and the renowned illustrator Ernie Colón tell the story of the United States through the major speeches, laws, proclamations, court decisions, and essays that shaped it. The Great American Documents:Volume I introduces as series narrator none other than Uncle Sam, who walks us through twenty essential documents. Each document gets a chapter, in which Uncle Sam explains its key passages, its origins, how it came to be written, and its impact. This graphic primer is an indispensable resource for students and any one else who wants the facts of American history close at hand"--